﻿Preferential presence in harbours confirms the non-indigenous species status of Ammonia confertitesta (Foraminifera) in the English Channel - Jean-Charles Pavard; Vincent M. P. Bouchet; Julien Richirt; Apolyne Courleux; Eric Armynot du Châtelet; Gwendoline Duong; Romain Abraham; Jean-Philippe Pezy; Jean-Claude Dauvin; Laurent Seuront (Aquatic Invasions, 2023)
Though the morphological discrimination of the three pseudo-cryptic Ammonia species, A. aberdoveyensis, A. confertitesta and A. veneta, has been recently established, information on their ecology and habitats are still relatively scarce. This study aims to define distribution patterns of these species at eight sites scattered along the French coasts of the English Channel, over a total of 39 stations. These sites were classified into two habitats, either harbours (heavily modified sites) or less impacted (moderately influenced sites). The use of IndVal index (an index based on how a species is statistically specific to a habitat) clearly indicates that A. confertitesta is recorded preferentially in or close to harbours. Considering its non-indigenous species (NIS) status in Europe, we investigated its reported occurrences in Europe in the literature. It almost always showed a proximity to major European harbours. Sometimes, this species occurred relatively far away from these harbours, suggesting a secondary spread. Finally, this work interprets A. confertitesta being a NIS in the eastern English Channel with assumptions of being invasive regarding its dominance over the indigenous species A. aberdoveyensis and A. veneta. Complementary works such as retrospective core studies of fossil faunas are needed to quantitatively assess when and where A. confertitesta was introduced in Europe and potentially started to replace its congenerics A. veneta and A. aberdoveyensis.